2016
DOI: 10.5688/ajpe80116
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Paper vs Virtual Simulated Patient Case on Student-Perceived Confidence and Engagement

Abstract: Objective. To evaluate online case simulation vs a paper case on student confidence and engagement. Design. Students enrolled in a pharmacotherapy laboratory course completed a patient case scenario as a component of an osteoarthritis laboratory module. Two laboratory sections used a paper case (n553); three sections used an online virtual case simulation (n581). Student module performance was assessed through a submitted subjective objective assessment plan (SOAP) note. Students completed pre/post surveys to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 17 publications
4
44
0
3
Order By: Relevance
“…8,18 Self-assessment requires practice and experience. 10,11,19,20 Satheesh et al previously reported that student-faculty reliability was weak, 18 while Abe et al reported that self-assessment scores using rubric sheets were higher the second time compared with the first and that experience led to higher self-assessment scores. 11 The training course described in the present study represented the first opportunity for undergraduate students in 2014 and 2015 to assess their own performance using rubric sheets.…”
Section: Discussionmentioning
confidence: 99%
“…8,18 Self-assessment requires practice and experience. 10,11,19,20 Satheesh et al previously reported that student-faculty reliability was weak, 18 while Abe et al reported that self-assessment scores using rubric sheets were higher the second time compared with the first and that experience led to higher self-assessment scores. 11 The training course described in the present study represented the first opportunity for undergraduate students in 2014 and 2015 to assess their own performance using rubric sheets.…”
Section: Discussionmentioning
confidence: 99%
“…Learning was also assessed subjectively, through pre-, mid-and post-intervention surveys in twenty-six (46.4%) studies [11,12,[14][15][16][17][18][19]23,25,29,30,35,37,[41][42][43]45,46,50,52,56,57,59,62,64] and all but two [19,42] of these studies reported that the e-learning intervention was effective. Taglieri et al, [19] investigated the effect of completion of online virtual patient cases on student performance and confidence in mock clinic visits.…”
Section: Interventionmentioning
confidence: 99%
“…Of the fifty-six studies that were reviewed, all were limited by methodological flaws. Thirty (53.6%) studies [11,12,[14][15][16][17]19,20,22,[27][28][29][30][31][32][33][35][36][37]43,46,47,49,[52][53][54]56,58,63,64] did not establish the baseline knowledge, confidence or skills of participants and this is significant in two regards: It does not allow accurate comparison between groups, as differences in baseline knowledge may be responsible for differences in final knowledge; and it does not allow the impact of the intervention in increasing students' performance to be quantified. Three (5.4%) [25,55,57] of the nine studies that reviewed blended learning methods, failed to assess the effectiveness of the e-learning intervention independently of the face-to-face teaching.…”
Section: Limitations Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations